A Canadian Massage Therapy Education Environmental Scan - Baskwill, PhD, MSc, BEd, RMT, Amanda; Sumpton, BScN, Bryn; Shipwright, BA(Hons), RMT, Stacey; Atack, PhD, Lynda; Maher, PhD, Janet (International Journal of Therapeutic Massage & Bodywork, 2020)
Background: Massage therapists have been a part of Canadian’s health care since 1919. The profession has gone through great change over the past 100 years including adjustments to entry-to-practice education. An important recent change was the implementation of massage therapy (MT) education program accreditation. In light of the likely disruption as a result of programs becoming accredited, a scan of the current state of MT education in Canada was undertaken. Methods: An environmental scan informed by seminal medical education efforts was used to describe the thoughts and opinions of MT education stakeholders in Canada. Specifically, stakeholders were interviewed regarding the current state of MT education and their comments were analyzed for common themes. Results: Twenty-one stakeholders participated. Four themes were constructed: variation, isolation, stagnation, and accreditation. Variation is described as the impact of differences in content and quality of the education provided in MT colleges. Isolation is described as the feeling of the participant being separated, or disconnected, from the regulator, accreditor, or colleagues due, at least in part, to a lack of communication or networking opportunities. Stagnation is described as a lack of activity, growth, or development within MT education. Participants talked about accreditation, both as a solution for some of the challenges previously mentioned, and as a potential challenge in itself. Conclusions: Several challenges to MT education were described by stakeholders that they hoped would be remedied by national MT program accreditation. Despite some limitations, this environmental scan forms a baseline for stakeholder views on massage education in Canada upon which future comparisons can be made. While the environmental scan results are most useful when applied to the MT in Canada context, stakeholders in other countries may also find them interesting and valuable when considering challenges facing their own education programs.